Being Young, Male and Muslim in Luton - Hoque, Ashraf (Book collections on Project MUSE., 2019)
What is it like to be a young Muslim man in post-7/7 Britain, and what impact do wider political factors have on the multifaceted identities of young Muslim men? Drawn from the author's ethnographic research of British-born Muslim men in the English town of Luton, Being Young, Male and Muslim in Luton explores the everyday lives of the young men and, in particular, how their identity as Muslims has shaped the way they interact with each other, the local community and the wider world. Through a study of religious values, the pressures of masculinity, the complexities of family and social life, and attitudes towards work and leisure, Ashraf Hoque argues that young Muslims in Luton are subverting what it means to be 'British' through consciously prioritising and re-articulating self-confessed 'Muslim identities' in novel and dynamic ways that suit their experiences as a post-colonial diaspora. Employing extensive participant observation and rich interview content, Hoque paints a detailed picture of young Muslims living in a town consistently associated in the popular media with terrorist activity and as a hotbed for radicalisation. He challenges widely held assumptions about cultural segregation, gender relations and personal liberty in Muslim communities, and gives voice to an emerging generation of Muslims who view Britain as their home and are very much invested in the long-term future of the country and their permanent place within it. This short and accessible book will be of interest to students seeking grounding in Islam and Muslim communities in diaspora, and scholars from an array of social science and humanities backgrounds including Anthropology, Sociology of Religion, Political Science, Urban Studies and Cultural Studies.